Epidemiology of drug resistance and evaluation of possible mechanical transmission of Trypanosoma congolense by haematophagous insects in Zambezia Province Mozambique - Neves, Luís C.B.G. (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.